Ekstraksi Pewarna Alami Daun Suji, Kajian Pengaruh Blanching dan Jenis Bahan Pengekstrak - Putri, Widya Dwi Rukmi; Zubaidah, Elok; Sholahudin, N. (Fakultas Teknologi Pertanian Universitas Brawijaya, 2003)
Natural pigment involved in suji leaves (Pleomele angustifolia) is chlorophyll. Extraction of this pigment needs specific solvent. This research studies the effect of blanching and the kind of solvent i.e water, alcohol 85 % and acetone 85 %. The result showed there is no significant interaction to chlorophyll total, pH, chlorophyll total cause of heating in temp. 100oC and pH 4,5.Â The highest chlorophyll total can reach by extraction with acetone 85 % and without blanching i.e 12,03 mg/l and 10,84 mg/l. Â Keyword: natural pigment, Pleomele angustifolia, pertanian , extraction, and chlorophyll